2017
DOI: 10.1155/2017/6463586
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Effects of Parking Charge and Supply Policy Using System Dynamics Method

Abstract: Reasonable parking charge and supply policy are essential for the regular operation of the traffic in city center. This paper develops an evaluation model for parking policies using system dynamics. A quantitative study is conducted to examine the effects of parking charge and supply policy on traffic speed. The model, which is composed of three interrelated subsystems, first summarizes the travel cost of each travel mode and then calibrates the travel choice model through the travel mode subsystem. Finally, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Similarly, Brand et al [7] conducted a scenario study to assess car pricing and taxation instruments, and suggested car purchase feebate policies are effective in accelerating the uptake of low-carbon technology and reducing life cycle greenhouse gas emissions. It was also confirmed that parking policy is a necessary measure to control urban road demand, and that a customized parking charge policy could address the phenomenon of parking difficulty in cities [8,9]. Pu et al [10] reported that the restrictions on car licenses in Hangzhou would restrict the vehicles with certain license numbers from entering the downtown area during peak hours, and therefore effectively reduce the car emissions in the restriction area.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Similarly, Brand et al [7] conducted a scenario study to assess car pricing and taxation instruments, and suggested car purchase feebate policies are effective in accelerating the uptake of low-carbon technology and reducing life cycle greenhouse gas emissions. It was also confirmed that parking policy is a necessary measure to control urban road demand, and that a customized parking charge policy could address the phenomenon of parking difficulty in cities [8,9]. Pu et al [10] reported that the restrictions on car licenses in Hangzhou would restrict the vehicles with certain license numbers from entering the downtown area during peak hours, and therefore effectively reduce the car emissions in the restriction area.…”
Section: Introductionmentioning
confidence: 84%
“…Researchers have engaged in conducting studies to evaluate the effectiveness and public acceptance of policies in the transport field. Some scholars evaluated and examined isolated transport policies instead of from a comprehensive perspective [4,5,9]. Some explored the different public acceptance of green transport policies in different countries and regions at different times [20,21].…”
Section: Framework and Hypothesesmentioning
confidence: 99%
“…In the case of unrestricted parking, the study revealed that the average travel speed would be reduced up to 16%, with traffic system performance at its best with very high prices compared with a zero-price option. Furthermore, an agent-based simulation case study in the central business district of the city of Wulin (Hangzhou, China), compared three tactics—different parking lots at the same rates, different parking lots with different rates always, and different parking lots with different rates during peak hours—to discover which performed the best ( 20 ). The main findings were that: (i) for the two strategies with varying parking prices, there were improvements in average travel time, average travel distance, and failure rate (percentage of cruising vehicles), (ii) varying parking prices can disperse drivers to less popular parking areas, which means parking resources are used more effectively, and (iii) the best performing parking strategy was where parking prices were varied only at peak times, which had the best comprehension (i.e., combination of low average cost and failure rate).…”
Section: Literature Reviewmentioning
confidence: 99%